To find \( f(-2) \) for the function \( f(x) = 3x + 8 \), substitute \(-2\) for \(x\):
\[ f(-2) = 3(-2) + 8 \] \[ f(-2) = -6 + 8 \] \[ f(-2) = 2 \]
Thus, \( f(-2) = 2 \).
3 answers
To find \( f(-2) \) for the function \( f(x) = 3x + 8 \), substitute \(-2\) for \(x\):
\[ f(-2) = 3(-2) + 8 \] \[ f(-2) = -6 + 8 \] \[ f(-2) = 2 \]
Thus, \( f(-2) = 2 \).
Certainly! Let's go through each step in detail to find \( f(-2) \) for the function \( f(x) = 3x + 8 \).
The given function is:
\[ f(x) = 3x + 8 \]
To find \( f(-2) \), we need to substitute \(-2\) into the function wherever there is an \(x\):
\[ f(-2) = 3(-2) + 8 \]
Now, calculate \(3 \times -2\):
\[ f(-2) = -6 + 8 \]
Next, add \(-6\) and \(8\):
\[ f(-2) = -6 + 8 = 2 \]
So, the value of \( f(-2) \) is:
\[ f(-2) = 2 \]
This completes the calculation step-by-step.